Effect of Glutamic Acid Foliar Application Concentrations on Growth and Yield Traits of Two Genotypes of Roselle (Hibiscus Sabdariffa L.) - Yaseen Obaid Noori Ahmed Sharif; Satar Abid Khaleefh; Sura Hameed Bahar AL-Janabi; Hiba jomaa Alfahdawi; Tariq Raad Thaer Al-Mafarji (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2025)
A field experiment was conducted during the summer season of 2024 in the fields of a farmer in the Koldara area, affiliated with Altun Kupri sub-district in Dibis district, located in northern Kirkuk Governorate (35o44'45.5